Prevalence and Possible Causes of Infertility in the Perm Region - A. P. Godovalov; N. V. Nikolaeva; T. I. Karpunina (Эпидемиология и вакцинопрофилактика, 2019)
The aim of investigation was to assess the characteristics of the epidemic process of the incidence and prevalence of infertility and gonococcal infection, taking into account the demographic situation in Perm region.Materials and methods. The official statistics of the Center for Hygiene and Epidemiology in the Perm Region for 2003–2017 were analyzed (form 2), the territorial body of the Federal State Statistics Service in the Perm Region. The long-term dynamics of general morbidity, distribution of the patients by age, sex, social status, morbidity in combination with HIV infection, the detection of gonococcal infection by various specialists and methods of laboratory diagnostics were studied using the method of retrospective epidemiological analysis. Statistical processing was carried out using the program Statistica 7.0. To determine the relationship between the individual parameters, a simple correlation analysis was used with the calculation of the conjugacy coefficient of the Pearson traits (r).Results. In the Perm region, despite the positive rate of natural population growth, the number of inhabitants in 2010-2016 decreased by 14.5 thousand people. Every year the number of women in adolescent and youthful age falls. It has been shown that the leading factor in the formation of infertility is inflammatory diseases of the reproductive organs and the presence of comorbid pathology. It was established leading value in the pathogenesis of infertility of gonococcal infection. The features of the epidemic process of gonorrhea in the Perm region was shown.Conclusion. In a large number of cases, the complication of the demographic situation in the province is associated with infection of the genital tract. It is necessary to use more widely the possibilities of microbiological diagnostics.